Pre‐transplant short physical performance battery: Response to pre‐habilitation and relationship to pre‐ and early post–lung‐transplant outcomes - Wickerson, Lisa; Rozenberg, Dmitry; Gottesman, Chaya; Helm, Denise; Mathur, Sunita; Singer, Lianne G. (Clinical transplantation, 2020)
Purpose To evaluate whether the short physical performance battery (SPPB) pre‐lung transplant (LTx) was responsive to pre‐habilitation and predicted pre‐ and early post‐transplant outcomes. Methods A retrospective study of LTx candidates accepted for transplant between 2016 and 2017. SPPB was categorized as frail/pre‐frail (≤9/12) and non‐frail (≥10/12). Results 150 patients had LTx assessment SPPB data (53% male, 61 [52‐67] years, 59% had interstitial lung disease (ILD), 26% frail/pre‐frail). 131 (87%) underwent transplant by December 31, 2018. Adjusting for age, sex, diagnosis and Canadian transplant listing urgency, and frailty/pre‐frailty at LTx assessment was associated with a lower 6MWD pre‐transplant [−89 meters 95%CI (−125 to −53), P < .0001]. 62 patients underwent six weeks of pre‐habilitation. SPPB increased (11 [10‐12) vs. 12 [11‐12], P = .01) reflected in the chair stand component (11.4 ± 4.4 vs. 9.8 ± 2.8 seconds, P = .007), with larger improvements in the frail/pre‐frail group. A frail/pre‐frail SPPB closest to the time of transplant was associated with a lower 6MWD [−77 m 95%CI (−128 to −25), P = .004] but not with hospital length of stay or gait aid use three months post‐transplant. Conclusions Frailty/pre‐frailty was associated with a decreased 6MWD pre‐ and post‐transplant. The SPPB increased following pre‐habilitation, which may reflect increased lower extremity strength.